Avaliação do perfil sociodemográfico, qualidade de vida e a gravidade da incontinência urinária em policiais militares femininas que atuam no município de Macapá, Amapá - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2023)
Urinary incontinence (UI) is the condition in which the individual loses urine involuntarily, directly affecting quality of life and has three main classifications: stress UI, urge UI and mixed UI. Objective: The study carried out had the general objective of verifying whether female military police women in the city of Macapá have a significant UI and if this affects their quality of life. Method: This is a descriptive, cross-sectional study with a quantitative approach, developed with women police officers who work in the Military Police of the state of Amapá. Carried out in two stages, in which an informative lecture was held in the first stage and a socio demographic questionnaire was applied and, based on self-report of UI in this questionnaire, the participants would be able to continue in the research. The second and last step used the application of two specific questionnaires for UI, the ICIQ-SF that assesses the severity and impact of UI, and the KHQ that weighs the impacts of UI related to quality of life. Results: 23 women participated in the research, but 12 were able to continue in the study, these were women with an average age of 35 years ± 10.7 years, most married/stable union with 75%, of the participants 91.7% have complete higher education, highlighting that 58.3% of women are between 25.0 and 29.9 kg/m² classified as overweight. Regarding the prevalence, 52% of the participants had UI, with 58.3% classified with stress UI and overactive bladder demonstrating urinary leakage by both mechanisms, and 16.7% with urgency UI. In the KHQ quality of life questionnaire, 66.7% of women do not consider it a problem to lose urine. The participants had the worst performance for the domains of Health Perception (29.17), Measures of Severity (15.97), Sleep/energy (13.98), Impact of Incontinence (13.89), Limitations of Daily Activities ( 12.5). Finally, the average total score of the ICIQ-SF was 2.9 points, which represents 13.86% of the questionnaire score, which indicates that in the KHQ and ICIQ-SF, UI had a relatively low impact on quality of life. participants' lives. Conclusion: In the present study, a high prevalence of female military police officers with UI was observed, affecting them regardless of the age at which they were diagnosed based on their reports. They had several lifestyle habits that are factors that are considered risks for the onset and worsening of UI. Our findings demonstrated that there are no significant impacts on the quality of life of these women, which is why more studies are needed in the evaluated public, with even more reliable tools for a more objective evaluation.
Keywords: Polícia Militar; Mulher; Incontinência urinária; CNPQ::CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; ODS 3 – Saúde e bem-estar